Fundamental and experimental aspects of diffraction for characterizing dislocations by electron channeling contrast imaging in scanning electron microscope - Kriaa, H. (Sci Rep, 2017)
Nowadays Field Emission Gun-Scanning Electron Microscopes provide detailed crystallographic information with high spatial and angular resolutions, and allow direct observation of crystalline defects, such as dislocations, through an attractive technique called Electron Channeling Contrast Imaging (ECCI). Dislocations play a crucial role in the properties of materials and ECCI has naturally emerged as an adapted tool for characterizing defects in bulk specimen. Nevertheless, fine control of the channeling conditions is absolutely required to get strong dislocation contrast for achieving comprehensive analysis. In this work, experiment-assisted fundamental aspects of the origin of dislocation contrast are studied. Experimentally, the potential of ECCI is explored in several dislocation configurations in Interstitial-Free steel (Fe − 1% Si) used as a model material. Full interpretations of dislocation contrast in (g, −g) and its evolution along the Kikuchi band are shown. Furthermore, a dislocation dipole is observed and fully characterized for the first time in an SEM.